1988
DOI: 10.1177/106002808802200318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Contribution of Clinical Pharmacists: Inpatient Care and Cost Reduction

Abstract: Clinical pharmacists in this study hospital reported 1027 interventions in patient drug therapy over two time periods of three and two weeks, respectively. These interventions were subjected to self and peer reviews and to cost-avoidance evaluation. The most frequent type of intervention was recommendations related to drug selection (29.6 percent). Recommendations were not implemented by physicians in only 10.2 percent of the cases. The perceived impact of these interventions on the quality, cost, or both was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 3 publications
6
82
1
1
Order By: Relevance
“…Wernick and colleagues (1996) conducted a six-week study which evaluated the frequency and types of variances that occurred in patients' discharge prescriptions. Their study reported that 11.9% of the participating patients' discharge prescriptions contained a variance that required an intervention, and, using the same Intervention Ranking system (Hatoum et al 1988), 48.6% of pharmacist interventions were categorized as significant (Wernick et al 1996). As discussed by others (Schumock et al 1994;Wernick et al 1996), comparing rates of prescription discrepancies between studies can be difficult when each study does not use the same definition of discrepancy and the same identification methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wernick and colleagues (1996) conducted a six-week study which evaluated the frequency and types of variances that occurred in patients' discharge prescriptions. Their study reported that 11.9% of the participating patients' discharge prescriptions contained a variance that required an intervention, and, using the same Intervention Ranking system (Hatoum et al 1988), 48.6% of pharmacist interventions were categorized as significant (Wernick et al 1996). As discussed by others (Schumock et al 1994;Wernick et al 1996), comparing rates of prescription discrepancies between studies can be difficult when each study does not use the same definition of discrepancy and the same identification methods.…”
Section: Discussionmentioning
confidence: 99%
“…All of the DTPsm were scored for their potential clinical impact according to the Intervention Ranking system (Hatoum et al 1988). Other researchers have used this scale to evaluate the clinical impact of pharmacists' interventions (Wernick et al 1996).…”
Section: Drug-therapy Problems Inconsistencies and Omissions Ann Nicmentioning
confidence: 99%
“…Drugrelated problems associated with inappropriate dosing occur in individuals with renal insufficiency or failure, and pharmacists have documented positive outcomes through drug management and other innovative programs for this population. [83][84][85][86][87][88][89][90][91][92][93][94][95][96] Documented Impact…”
Section: Pharmacy' S Positionmentioning
confidence: 99%
“…1 Currently, direct patient care by clinical pharmacists within multidisciplinary teams is recognized as one of the best pharmacy practice models because it minimizes risks, care costs, morbidity and mortality rates, as well as time spent in hospital; it also improves pharmacotherapy results. [2][3][4][5][6][7][8][9] Several initiatives and standards of practice for clinical pharmacy have been proposed around the world. These proposals promote the transformation of clinical pharmacy services through participation of pharmacists as providers of direct patient care, counselling, and support to medical and nursing staff in their decision-making.…”
Section: Introductionmentioning
confidence: 99%